STUDY OF SOCIOLOGICAL DETERMINANTS FOR THE SUCCESS OF ENVIRONMENTAL EDUCATION AROUND THE MANAGEMENT OF HOUSEHOLD WASTE IN COTONOU - GBENOU, V. Victorin (My University, 2017)
Study of sociological determinants for the success of environmental education around the household waste management in Cotonou The rapid urbanization and the demographic pressure at Cotonou, have caused an accumulation of housework’s solids wastes and constituted some of the high factors of environment deterioration and urban populations healthy of these economic capital of Benin. The management of these homework’s wastes is consequently one problem does this urban habitants were confronted. This study aims to determine the sociologic factors how can contributed on the betters managements knowledge’s of Cotonou homework’s wastes and the effects of these wastes in environment and populations health. The methodology used on this study based on the variables who can explain socioeconomics gravity that slowed the good socioeconomics management of homework’s waste at Cotonou. These factors were treated in descriptive and multifactor’s analyses in order to correlate the factors. Results of these investigations showed that in spite of presence of collected and evacuate structures, the solids wastes management was mediocre. This way is not without effects on populations health and on the environment.
Keywords: solids wastes; management; environment and sanitary impacts; Cotonou.